Bridge Collaborative practitioner’s guide: Principles and guidance for cross-sector action planning and evidence evaluation - Tallis, Heather; Kreis, Katharine; Olander, Lydia; Ringler, Claudia; Zhang, Wei (Duke University, 2017)
This document captures a set of principles identified and used by the Collaborative, along with a detailed set of guidance for creating comparable results chains across sectors and evaluating evidence from multiple disciplines in common terms. These principles and guidance reflect novel contributions from the Bridge Collaborative as well as restatements of existing recommendations that resonated among health, development and environment researchers and practitioners.